Strip Sampling in Nersol Slopes Forest - Mokashi, V. K. (Indian Forester, 1955)
Complete enumerations were carried out in 1942 in the Nersol Slopes Forests. Different species were enumerated by strips as sound and unsound. Total number of sound trees of teak on a strip was treated as a variate. The eight compartments for which the data were available, were treated as strata. The analysis of the data was carried out and was used to find out the sample size for stratified random sampling with (1) optimum allocation and (2) proportional sampling in strata. The former was found to be efficient than the latter. The sampling intensity required to estimate the total number of sound trees of teak with 8% standard error amounted to 6 to 7 per cent of the total number of strips. If sampling work is extended to all the seventeen compartments, the sampling intensity could be considerably reduced for the same precision.